Pengaruh Kepercayaan Konsumen dan Barang Image terhadap Keputusan Pembelian Online Shop Lazada (Studi Kasus pada Mahasiswa Institut Ilmu Sosial dan Manajemen STIAMI Kampus Pusat) - Bagas Prastowo; Suhenda Adia (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The research objective was to determine the effect of consumer trust and brand image on purchasing decisions on STIAMI Central Campus Institute of Social Sciences and Management students. This study uses quantitative research on 98 respondents using accidental sampling techniques. The type of research in this study is field research and library research. The type of data used in this study was obtained from primary data and secondary data. Data collection methods used were observations and questionnaires. The data analysis technique used in this study tested the validity, reliability, correlation coefficient and determination, multiple linear regression and hypothesis testing. The results of the study show that simultaneous consumer trust and brand image influence purchasing decisions.